Evaluation of the penetration of chlorides in concrete elements in the city of Pelotas / RS - Ferreira, Carina Farias; Paliga, Charlei Marcelo; Torres, Ariela da Silva (Revista ALCONPAT, 2018)
This research aims to verify the compatibility of an existing predictive model of life with the penetration of chlorides in exposed concrete elements in the city of Pelotas / RS. To this end, the samples were exposed at different locations in the city for a period of 16 months and silver nitrate solution was applied to determine the depth of the chlorides. The Bob model (1996) was used for comparison and analysis of the results. Significant values of chloride were found in the elements and a great potential of the model applied when describing the behavior of the depth of chlorides over time, despite the differences found.